Design and Performance Analysis of a Two Loop Control for a PWM dc-dc Buck Converter - Bhagiya, R.D; Patel, R.M (International Journal of Computer Sciences and Engineering, 2025)
In this paper, a two loop control strategy based on frequency domain measures is proposed for a PWM dc-dc buck converter to regulate the output voltage in the presence of input voltage disturbances and load variations. The parameters of inner PI controller and outer PI controller for a specified phase margin and gain cross over frequency are designed using the proposed algorithm. State space averaging technique is used for the modeling of a PWM dc-dc buck converter. The effectiveness of the proposed control strategy is validated using MATLAB/Simulink software for different input voltages and loads